Attlee a life in politics - Thomas-Symonds, Nicklaus (London I.B. Tauris, 2012)
Clement Attlee - the man who created the welfare state and decolonized vast swathes of the British Empire, including India - has been acclaimed by many as Britain's greatest twentieth-century Prime Minister. Yet somehow Attlee the man remains elusive and little known. How did such a moderate, modest man bring about so many enduring changes? What are the secrets of his leadership style? And how do his personal attributes account for both his spectacular successes and his apparent failures? When Attlee became Prime Minister in July 1945, he was the leader of a Labour party that had won a landslide victory. With almost 50% of the popular vote, Attlee seemed to have achieved the platform for Labour to dominate post-war British politics. Yet just 6 years and 3 months after the 1945 victory, and despite all Attlee's governments had appeared to achieve, Labour was out of office, condemned to opposition for a further 13 years. This presents one of the great paradoxes of twentieth-century British history: how Attlee's government achieved so much, but lost power so quickly. But perhaps the greatest paradox was Attlee himself. Attlee's obituary in The Times in 1967 stated that "much of what he did was memorable; very little that he said." This new biography, based on extensive research into Attlee's papers and first-hand interviews, examines the myths that have arisen around this key figure of British political life and provides a vivid portrait of the man and his politics.
Originally published: London ; New York : I.B. Tauris ; New York : Distributed In the United States by Palgrave Macmillan, 2010.
Keywords: Attlee, C. R. (Clement Richard), 1883-1967.